Utilization of ATP and Its Derivatives as an Index of Freshness of Nila (Oreochromis niloticus) During Storage - Djagal W Marseno; Sudarmanto Sudarmanto; Retno Indrati (Indonesian Food and Nutrition Progress, 1999)
The role of a reliable and reproducible, index of fish freshness, is important. The objective of this research was to examine the utilisation of ATP and its derivatives (expressed as K-value) as an index offish freshness using Nila (Oreochromis niloticus) as a model of study. K-value is [(Inosine + Hypoxanthine) / (ATP + ADP + AMP + IMP + Inosine + Hypoxanthine)] x 100%. Live fish were killed, packed individually using polyethylene bag and stored at 4 and 28°C. At defined time, some fishes were examined their ATP and its breakdown products using a reverse phase HPLC system. The results showed that ATP, ADP and AMP were degraded rapidly and disappeared within 12 ho urs. Degradation of IMP in the samples stored at 4°C was slower than those of samples stored at 28°C. Interestingly, the accumulation of Inosine occurs only in the samples stored at 28°C while the accumulation of Hypoxanthine occurs only in the samples stored at 4"C. The data suggested that the activity of IMP-degrading enzyme (5'-nucleotidase) at 4"C was higher than that of Inosine-degrading enzyme, but at 28°C both enzymes have similar activities. Linear regression analysis between K-value and storage time showed that increasing rate of K-value or rate of the lowering freshness of samples stored at 28"C was 4 times higher than that of samples stored at 4°C. Limits offish acceptability (K-value 60%) of Nila stored at 28 and 4"C were reached at 12 and 72 hours, respectively. The results confirmed that K-value was the best as an index offish freshness compared with IMP, Inosine and Hypoxanthine and it could be used as an index of freshness of Nila (Oreochromis niloticus) during storage.